Research and experimental analysis on precision degradation of BSM at low speed(Ⅰ):theory analysis - KONG Deshun; GAO Xiangsheng; LI Shilin; LV Linbao (高技术通讯（英文版）, 2024)
In the structure of double-nut ball-screw mechanism(BSM),the contact angle of the ball-screw determines the relative positional relationship between the balls and the screw as well as the nut.The contact angle is related to geometrical parameters of the ball,the screw and the nut,which are also affected by the running status and the preload of the BSM.Considering the effect of the gy-roscopic moment on the ball in the raceway,the dynamic model of the ball in space is established under different speeds and different preloads of the BSM.By simulation of the dynamic model of the ball in space,the changing regularity of the contact angle,the helix angle,the drag torque and the mechanical efficiency of the BSM can be obtained under different speeds and different preloads.The results show that there is a nonlinear gradient relationship between contact angle,helix angle,the drag torque,the mechanical efficiency and the speeds of the ball-screw under different preloads.The contact angle is the key factor to affect the drag torque of the BSM.Through the analysis,it is found that establishing the ball dynamic model in space can better study the precision degradation law of the ball screw.